PENCATATAN IDENTIFIKASI DAN REKAM KESEHATAN PERSONAL SISWA DI SMPN 7 KOTA BAUBAU - Niska Salsiani Sinta (Universitas Borneo Tarakan, 2023)
In the world of education, medical records become quite vital in the context of administrative and documentation aspects. In terms of administration, the existence of health records can make it easier for teachers or UKS managers to store and search for files related to student health. Activity This community service is carried out as a regular activity that is usually done by lecturers every semester. The service team chose SMP N 7 Baubau City as the object of community service due to the location affordable, inadequate school health unit (UKS) facilities and students still need counseling to increase knowledge about recording personal health.Community service activities are carried out using the presentation/lecture method, the presentation is carried out for approximately 30 minutes. Participants were given information about the importance of recording student health identification and personal health records. In the Student Identification and Health Data Recording Program, participants were given an explanation on how to record the correct identification according to the family card and the importance of correct identification. In this activity, participants were given an example of a student index card to make it easier to find student health data. This activity is expected to improve the quality of UKS and the orderly administration of an educational institution, making it easier for UKS supervisors to search for student health data. is also a source of information for research in the health sector, and can be used as research material for academics who need it